Experimental and computational data set on adsorption of Cr (VI) from water using an activated carbon (2020)
Chromium (Cr) is a widely used metal in metallurgical and chemical industries, whose waste contaminates the surface and groundwater. Cr (VI) is toxic and produces carcinogenic effects owing to its high mobility in water and soil. In this work, computational and experimental studies from the adsorption of Cr(VI) from aqueous solutions on teak wood residues activated with ZnCl2 (AT) are presented. Full interpretation of data can be found in DOI:10.1016/j.jece.2020.103702 [1]. Experimental data were adjusted to Langmuir, Freundlich and Temkin isothermal models and the nonlinear and linear forms of the Pseudo-first and Pseudo-second order kinetic models. Computational data allow to understand the adsorption process of Cr(VI) on carbonaceous materials. © 2020 The Author(s)